Should Caffeine Be Avoided Following Free Flaps: Fact or Fiction? - Dharmarajah, Nina; Chon, Jeewon; DiChiaro, Bianca; Bucholz, Eleanor (Journal of Reconstructive Microsurgery, 2025)
Many microsurgeons recommend that their patients avoid all compounds containing caffeine after free tissue transfer, however, there is little in the literature to implicate caffeine as a contributor to flap loss. While caffeine has historically been viewed as a vasoconstrictor that could theoretically impair flap perfusion, its physiological effects are complex, involving both vasoconstrictive and vasodilatory mechanisms. This review aims to determine whether caffeine consumption may increase flap-related complications including ultimate failure.A narrative review was conducted through PubMed and Google Scholar to evaluate the mechanism of action of caffeine. Articles were included if they provided insights into caffeine's mechanisms of action in the central nervous system, cardiovascular system, endothelium, and microcirculation.Caffeine causes the release of neurotransmitters in the CNS promoting wakefulness through the antagonism of adenosine receptors. In both smooth muscle and vascular endothelium, caffeine promotes vasodilation through the activation or inhibition of different types of receptors including adenosine, inositol triphosphate, and nitrous oxide. Studies in both human and animal models suggest that caffeine does not significantly affect microvascular perfusion or anastomotic patency. Data suggest that habitual caffeine consumers show blunted vascular responses, further mitigating concerns in flap outcomes.Despite current recommendations for caffeine restriction following free tissue transfer, the existing evidence does not support caffeine as a major risk factor for flap failure. Postoperative caffeine avoidance may be unnecessary, particularly for habitual users. Larger prospective studies are needed to further elucidate caffeine's role in microsurgical outcomes and to explore the effects of other stimulants, such as ADHD medications, on microvascular circulation.
Keywords: caffeine; microsurgery; free flap